Analysis of the Implementation of the Du Pont System on Financial Statements as a Tool for Measuring the Financial Performance of PT Bank Muamalat - Mas'amah, Siti; Sihabudin, Sihabudin; Fuji, Robby (CV. Rayyan Dwi Bharata, 2023)
In analyzing the financial performance of a bank or a company, you can use the two-point system method. The du point system is a chart designed to show the return on assets obtained by multiplying the profit margin by the total asset turnover. The purpose of this study is to find out the description of the financial performance of PT Bank Muamalat Kalimalang Karawang Period 2019-2021 using the two-point system method, PT Bank Muamalat Kalimalang Karawang is one of the branches of PT Bank Muamalat in Indonesia as a pioneer of Islamic banking in Indonesia. This research was conducted with quantitative methods. The object of this research is the audited financial statements of PT Bank Muamalat Kalimalang Karawang from 2019 to 2021. Data collection was carried out using the documentation method. The results of the analysis can be concluded that Net Profit Margin (NPM), Asset Turnover (ATO), Return On Assets (ROA), and Return On Equity (ROE), experience fluctuating positions or are in a state of flux whether there is an increase or decrease. The results of this study suggest that companies should be able to maximize the use of assets and minimize expenses so that companies can be consistent in measuring financial performance at PT Bank Muamalat Kalimalang Karawang.